(untitled) (Bulletin of Innovative Research, 2026)
The article examines the historical sources of the formation of mathematical terminology and analyzes the peculiarities of its functioning in modern English, Russian, and Uzbek. Despite the universality of the mathematical system, the linguistic representation of mathematical concepts demonstrates nationally specific features determined by the historical, cultural, and structural factors of each language’s development. The study covers the etymological analysis of key terms, the comparison of word-formation models, semantic classification, and the peculiarities of term usage in scientific and general-language discourse. The findings reveal that English mathematical terminology is predominantly based on the Greco-Latin tradition and is characterized by a high degree of international standardization; the Russian system is marked by the adaptation of internationalisms and a well-developed derivational model; Uzbek terminology demonstrates a synthesis of Arab-Persian heritage, Russian borrowings, and productive agglutinative derivation. The results confirm that mathematical terminology represents not only an instrument of scientific communication but also a reflection of cultural and linguistic specificity.